Transistor Level Implementation Of Led Driver For Solid State Lighting - Abdul Aziz, Siti Rohaya (2014)
This thesis presents the transistor level implementation of led driver for solid state lighting (ssl). Ssl refers to a type of lighting that uses semiconductor light emitting diodes, organic light emitting diodes (oled), or polymer light emitting diodes (pled) as sources of illumination. Led driver is an electrical device that provides required led voltage and regulates the constant amount of power to the needs of led or string of led. A buck converter is one type of dc- dc converter that can step down the dc input voltage to the required led voltage. In the high input voltage application of the rectified 220-240v ac, the modified buck converter technique has been applied instead standard buck that requires complicated design of bootsrap mode. The development of discrete led driver prototype is to prove the buck converter operation. This circuit design has been integrated with the led driver integrated circuit (ic) to provide a constant current output to the leds with the intention to decrease the size, weight and cost. The design of led driver ic is started with the behavioral modeling technique for proposed control circuit with integrated power switch, dmos. The obtained parameters from behavioral model have been implemented in the transistor level design using x-fab xdm10 1.0pm 350v process technology. In this project, leds string will be driven as much as 20 with the total forward voltage are 50-60v and the current is 350ma.